2017
DOI: 10.3389/fmars.2017.00239
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Foraging Tactics of Marine Predators with Different Feeding Strategies across Heterogeneous Ocean Environments

Abstract: Advances in satellite tracking and archival technologies now allow marine animal movements and behavior to be recorded at much finer temporal scales, providing a more detailed ecological understanding that can potentially be applicable to conservation and management strategies. Pelagic sharks are commercially exploited worldwide with current concerns that populations are declining, however, how pelagic sharks use exploited environments remains enigmatic for most species. Here we analyzed high-resolution dive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 92 publications
(166 reference statements)
3
28
0
Order By: Relevance
“…On the other hand, our results show that six manta rays remained at maximum depths for more than 10 minutes. These dive patterns are more akin to U-shaped profiles, suggesting the exploitation of aggregated prey [38,42]. As fishes, manta rays diving is not limited by the ability to store oxygen, but more probably by the low temperatures at these depths.…”
Section: Plos Onementioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, our results show that six manta rays remained at maximum depths for more than 10 minutes. These dive patterns are more akin to U-shaped profiles, suggesting the exploitation of aggregated prey [38,42]. As fishes, manta rays diving is not limited by the ability to store oxygen, but more probably by the low temperatures at these depths.…”
Section: Plos Onementioning
confidence: 92%
“…Analysis of dive profiles can provide valuable information on diving behaviour [38]. Classification of dive profiles has been mainly conducted on air-breathing marine animals such as seabirds [39], sea turtles [40], or seals [41], as well as a few studies focused on predatory fish [42,43].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Sims et al (2003) suggested that vertical movements were consistent with those associated with foraging, with animals likely feeding year round on zooplankton. These behaviours, however, differed with habitat type: when in deep stratified waters of the continental shelf-edge, basking sharks exhibited normal diel vertical migration (DVM; dusk ascent-dawn descent), but when in shallow, inner-shelf waters basking sharks conducted reverse diel vertical migration (rDVM; dusk descent-dawn ascent; Sims et al 2005;Stéphan et al 2011;Queiroz et al 2017). Basking sharks were also shown to switch behaviours to a tidal rhythm when encountering boundaries between thermally stratified and mixed waters (Shepard et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…, and was calculated here based on the SST data and using maximum gradient maps by determining where for each pixel a geodetic-distance-corrected maximum thermal gradient was identified; (iii) sea water salinity (psu) (SAL), an important determinant of habitat use in some sharks 1,38 ; (iv) sea surface height above geoid (m) (SSH) that influences shark presence 5 and catches by fisheries 6 ; (v) ocean mixed layer depth thickness or thermocline depth (m) (MLD) that affects pelagic shark foraging behaviour 39 ; (vi) mass concentration chlorophyll a in sea water (mg m -3 ) (CHL) as a proxy for productivity that often characterises preferred habitats of sharks5,39 ; (vii) mole concentration of phytoplankton expressed as carbon in sea water concentration (mmol m -3 ) (PHY) as a direct measure of productivity; (viii) net primary production of biomass expressed as carbon per unit volume in sea water per day (g m -3 d -1 ) (NPP) quantifying productivity; and (ix) mole concentration of dissolved molecular oxygen in sea water (mmol m -3 ) (DO) that can strongly influence shark space use 1 . Environmental datasets i to v were downloaded from Copernicus Marine Environment Monitoring Service (CMEMS) Global Ocean Physics Reanalysis product (https://bit.ly/2MOJeSy; downloaded November 2017) and datasets vi to ix from CMEMS Global Ocean Biochemistry Hindcast product (https://bit.ly/2TwNbOq; downloaded November 2017).…”
mentioning
confidence: 99%